Treatment of immunoglobulin-resistant kawasaki disease: a Bayesian network meta-analysis of different regimens - Pan, Yan; Fan, Qihong; Hu, Luoyi (Frontiers in Pediatrics, 2023)
Background: This study aimed to gather evidence from clinical trials on the efficacy and safety of the available treatments for intravenous immunoglobulin (IVIG)-resistant Kawasaki disease (KD) in children. Methods: This work adopted the Newcastle–Ottawa scale to analyse the quality of the enrolled articles. A network meta-analysis was performed using clinical trials that compared drugs used to treat IVIG-resistant KD. Aggregate Data Drug Information System software v.1.16.5 was employed to analyse whether infliximab, second IVIG infusions, and intravenous pulse methylprednisolone (IVMP) were safe and effective. Results: Ten studies, involving 704 patients with IVIG-resistant KD, were identified and analysed. Overall, infliximab exhibited remarkable antipyretic activity compared with the second IVIG infusions (2.46, 1.00–6.94). According to the drug rank, infliximab was the best option against IVIG-resistant KD. Regarding adverse effects, the infliximab group was more prone to hepatomegaly. A second IVIG infusion was more likely to result in haemolytic anaemia. IVMP treatment was more susceptible to bradycardia, hyperglycaemia, hypertension, and hypothermia. In addition, infliximab, IVMP, and the second IVIG infusions showed no significant differences in the risk of developing a coronary artery aneurysm (CAA). Conclusion: Infliximab was the best option against IVIG-resistant KD, and IVMP, infliximab, and second IVIG infusions have not significant differences of prevent CAA in patients with IVIG-resistant KD.